UMPSA, DBP make history with 8-hour nonstop patriotic poetry recital - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 28 August 2025 – The 8-Hour Poetry Recital Programme organised by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) in collaboration with Dewan Bahasa dan Pustaka (DBP) Central Region successfully showcased the art of poetry and elevated it as a medium of literary appreciation, arts, culture, and patriotic spirit.